Consciousness and the Mind-Brain-Body-World Relationship: Towards A Transdisciplinary and Transcultural Approach - Facco, Enrico; Fracas, Fabio; Tagliagambe, Silvano (Advances in Social Sciences Research Journal, 2023)
The aim of this paper is to overview the main epistemological implications of the scientific approach to consciousness and the mind-brain relationship, undergone a lively debate in the past decades by strict materialist monist and dualist stances. Their limits, as well as the limits of reductionism and the shortcomings of classical Western thought, suggest the need for a broader perspective. Actually, a transdisciplinary approach helps overcoming the limits and incompleteness of single axiomatic disciplines. Likewise, a transcultural, meta philosophical approach allows to understand key concepts and meanings common to different philosophies and cultures and properly face them beyond the multiplicity and ostensible oddity of forms. This approach seems to be appropriate in the study of consciousness and subjective phenomena, where the first-person perspective and the meaning of the experience are the condition sine qua non for their comprehension.